Multimodal Concepts for Integration of Cytotoxic Drugs - Brown, J. Martin; Mehta, Minesh P.; Nieder, Carsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Over recent decades, combined modality treatment has drastically improved the cure rates for various malignant tumors. Further progress is expected through the design of sound combinations involving recently developed drugs. The first part of this book summarizes the rationale and the preclinical data for combined treatment with ionizing radiation and pharmaceutical agents. Individual chapters focus on different forms of combined treatment, with due consideration being given to a range of drugs and to emerging combinations with small molecules and antibodies, derived from recent advances in molecular oncology. The second part of the book comprises a series of disease-specific chapters in which the clinical results of combined modality treatment are presented. In addition, the topics of acute and late toxicity, supportive treatment and tolerance in elderly patients are reviewed. All of the chapters have been written by basic scientists and clinicians who are acknowledged experts in the field. The text is specifically designed to be accessible to professionals from the various disciplines involved in multidisciplinary cancer care and to residents in radiation oncology training programs.
Preclinical Part -- Biological Basis of Combined Radio- and Chemotherapy -- Combinations of Antimetabolites and Ionizing Radiation -- Combinations of Taxanes and Ionizing Radiation -- Combinations of Topoisomerase Inhibitors and Ionizing Radiation -- Combinations of Hypoxia-Targeting Compounds and Radiation-Activated Prodrugs with Ionizing Radiation -- Combinations of Platinum Compounds and Ionizing Radiation -- Combinations of Cytotoxic Drugs, Ionizing Radiation, and Angiogenesis Inhibitors -- Combinations of Cytotoxic Drugs, Ionizing Radiation and EGFR Inhibitors -- Combinations of Cytotoxic Drugs, Ionizing Radiation, and Mammalian Target of Rapamycin (mTOR) Inhibitors -- Combinations of Ionizing Radiation and Other Sensitizing Agents -- Radiotherapy and Tumor-Targeted Drug Delivery -- Clinical Part -- Applications in Malignant Brain Tumors -- Applications in Head and Neck Cancer -- Applications in Esophageal and Gastric Cancer -- Novel Chemoradiation in Localized Pancreatic Cancer: Clinical Studies -- Applications in Lung Cancer -- Integration of Radiation Therapy and Systemic Therapy for Breast Cancer -- Applications in Rectal and Anal Cancer -- Concomitant Radiation and Chemotherapy in Muscle-Invasive Bladder Cancer -- Applications to Gynecological Cancers -- Early and Late Treatment-Induced Toxicity -- Feasibility of Combined Chemo- and Radiation Treatment in Elderly/Comorbid Patients.
Keywords: Medicine; Radiology; Radiotherapy; Respiratory organs -- Diseases; Oncology; Medical biochemistry; Surgery; Medicine & Public Health; Imaging / Radiology; Radiotherapy; Oncology; Medical Biochemistry; Surgery; Pneumology/Respiratory System; Electronic books